Factors Affecting the Mental Well-Being of Undergraduate Students in Karachi - Ismail, Zeenat; Shujaat, Neshmia (Advances in Social Sciences Research Journal, 2018)
This study explores the relationship of five variables commonly associated with mental wellbeing. The variables include perceived social support, family demands, socioeconomic status, gender and educational background. Mental well-being comprises of two subcomponents i.e. stress and depression and poor mental well-being is indicated by high scores on stress and depression and vice versa. The study further examines any significant associations the five variables have with one another. 208 undergraduate students from various universities across Karachi voluntarily responded to an online questionnaire. In agreement with our hypotheses, Pearson’s coefficient correlations showed all five variables had a significant relationship with mental well-being. However, the interrelations among the five variables were contrary to our predictions. Independent T tests revealed that males (M=20.45, SD=3.22, t (206) = 6.92) compared to females (M=16.92, SD= 4.09) perceived greater social support, especially from their friends. Females (M= 17.54, SD= 4.84) experienced greater family demands than males (M= 14.92, SD=3.70). Females also reported higher scores on depression (M=14.37, SD= 6.45) with a moderate effect size (eta squared=0.06), thereby suggesting a link between family demands and depression. Students from higher socioeconomic groups and non-mainstream educational backgrounds like the social sciences reported greater scores on stress and depression.